PENGARUH LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KINERJA PADA DINAS PENDIDIKAN KABUPATEN BANDUNG - Fajar Tri Sakti; Siti Masitoh (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The level of effectiveness in the 2015-2016 LRA is still not able to fully use the funds available at the Bandung District Education Office. Based on the research that that the Financial Report consisting of Performance Accountability in Bandung District Education Office is significant with 6.088 because t count 6.088> t table 2.040 then the results are "significant", with the conclusion because the value of t count> t table it can be said that Ho rejected means that the chance of error 0.05 or 5% can be concluded that the alternative hypothesis Ha is accepted, which means that the alternative hypothesis "Effect of Financial Statements on Performance Accountability in the Bandung District Education Office" is tested and acceptable.